A methodology for optimisation of solar dish-Stirling systems size, based on the local frequency distribution of direct normal irradiance. (1st December 2021) - Buscemi, A.; Guarino, S.; Ciulla, G.; Lo Brano, V.
Highlights: DNI hourly frequency distribution is analysed in 7 Mediterranean locations. Influence of DNI peak values on electricity production are investigated. Effects of redesigned and optimised aperture area of the collector are analysed. A new procedure using DNI frequency histograms to forecast energy production is presented. Solar data from PVGIS, an alternative to Meteonorm, was used to optimise reflector size. Abstract: In geographical areas where direct solar irradiation levels are relatively high, concentrated solar energy systems are one of the most promising green energy technologies. Dish-Stirling systems are those that achieve the highest levels of solar-to-electric conversion efficiency, and yet they are still among the least common commercially available technologies. This paper focuses on a strategy aimed at promoting greater diffusion of dish-Stirling systems, which involves optimizing the size of the collector aperture area based on the hourly frequency distributions of beam irradiance and defining a new incentive scheme with a feed-in tariff that is variable with the installed costs of the technology. To this purpose, a new numerical model was defined and calibrated on the experimental data collected for an existing dish-Stirling plant located in Palermo (Italy). Hourly-based simulations were carried out to assess the energy performance of 6 different system configurations located on 7 sites in the central Mediterranean area using two different solar databases: Meteonorm and PVGIS. A new simplified calculation approach was also developed to simulate the dish-Stirling energy production from the hourly frequency histograms of the beam irradiance. The results reveal that an optimised dish-Stirling system can produce 70–87 MWhe /year in locations with direct irradiation varying between 2000 and 2500 kWh/(m 2 ·year). The proposed incentive scheme would guarantee a payback time for investment in this technology of about ten years and the effect of economies of scale could lead, over the years, to a levelized cost of energy similar to that of other concentrating power systems.